Management control in fast growing entrepreneurial firms. Case study of four small and medium sized gazelles in Nordland county - Trondsen, Magne; Rakhimov, Mukhit (Nord universitet, 2016)
Masteroppgave i bedriftsøkonomi - Nord universitet, 2016